Design Of Workshops For The Management And Prevention Of Occupational Risks In Puichig- Mejía Agua Potable 2022 - Guaman, Brayan; Guerrero, Melany; Yanguicela, Karen (SCT Proceedings in Interdisciplinary Insights and Innovations, 2025)
The work that was developed in the Design of workshops for the management and prevention of occupational risks in Puichig-Mejía Agua Potable 2022, focused on the risks to which workers are exposed during their work activities. After conducting the surveys and seeing the results we can say that workers are exposed to different risks in their daily work activities due to different factors, either due to lack of communication between them, lack of order and cleanliness in the workplaces and lack of good risk control, among others.The main problem is that workers do not have knowledge about the different means of protection and prevention in different jobs. To counteract this problem, the solution of conducting workshops has been found of management and prevention of risks, which cover different topics such as: Basic safety rules, Correct use of EPPS, Correct management of equipment and tools, Basic rules of work coexistence, with the aim of making workers aware of these issues since in their daily routines they are exposed to serious risks. Currently, workers do not receive talks, sizes or training in their jobs about the activities they are going to perform, as well as the risks and accidents that are generated day after day, that is why the Risk Management and Prevention Workshops will be implemented to minimize the chances of incidents occurring in the workplace.